The effect of workplace bullying on burnout: the mediating role of affective well-being - Ribeiro, Neuza (2021)
Purpose This study aims to examine the impact of workplace bullying on employees' burnout by investigating the mediating effect of affective well-being (AWB). Design/methodology/approach Data of 532 employees from diverse organizations in Portugal were collected. These data were collected using anonymously completed structured questionnaires available online. Findings The results support the research hypotheses proposed, confirming that workplace bullying is related to both AWB and burnout. Moreover, affective workplace bullying partially mediates the relationship between workplace bullying and burnout, indicating that the victims have their AWB reduced, and, consequently, increase their burnout levels. Practical implications The findings suggest that organizations can foster employees' AWB and reduce the level of burnout by encouraging organizations to develop preventive policies and practices to safeguard against bullying at work. Originality/value To this date, only a few studies have examined mediating and moderating variables (Nielsen and Einersen, 2018) and none include AWB as a mediator of the relationship between workplace bullying and burnout. This study answers the call for further empirical research from those who have argued that more information is needed to understand the workplace bullying phenomenon and contributes to the growing debate on this topic and its effects on employees.